PENINGKATAN KEMANDIRIAN BELAJAR SISWA SMP MELALUI PEMBELAJARAN BERBASIS MASALAH - Tanti Jumaisyaroh Siregar (AXIOM : Jurnal Pendidikan dan Matematika, 2019)
The purposes of this research were to know: the difference of improvement in self-regulated learning of students that given problem-based learning with students that given direct learning. The type of this research is a quasi-experimental research by taking samples from the existing population. The variable of this research consist of independent variable that is problem based learning model while the dependent variable isself regulated learning of student.The population of this research is all students of SMP Swasta Ar-rahman Percut and the sample of this research is grade eight with taken sample two classes (experiment and control) with total 60 students. The instrument of this research were: scale of self-regulated learning. Data that have been collected then analyzed and performed hypothesis testing by using T-test. Based of the results analysis, it showed that: improvment of the students' self-regulated learning that given problem-based learning was higher than the students' ability that given direct learning His then, suggested that problem-based learning be used as an alternative for mathematic teacher to improved students' ability in mathematical critical thinking and self-regulated learning.